2013
DOI: 10.1016/j.chom.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and the Resulting Placental Vascular Insufficiency Drives Fetal Growth Restriction Associated with Placental Malaria

Abstract: Placental malaria (PM) is a major cause of fetal growth restriction, yet the underlying mechanism is unclear. Complement C5a and C5a receptor levels are increased with PM. C5a is implicated in fetal growth restriction in non-infection-based animal models. In a case-control study of 492 pregnant Malawian women, we find that elevated C5a levels are associated with an increased risk of delivering a small-for-gestational-age infant. C5a was significantly increased in PM and was negatively correlated with the angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 55 publications
8
138
0
2
Order By: Relevance
“…This hypothesis is supported by our data from the present and previous in vitro and in vivo studies (17,25) and by observations in human CM (5, 8-10, 17, 34, 43, 45, 46, 52). Furthermore, our observations are consistent with a growing body of compelling evidence implicating a causal role for C5a-C5aR in the induction of proinflammatory mediators and antiangiogenic factors in multiple disease conditions that share features with cerebral malaria, including sepsis, ischemia-reperfusion injuries, pathological angiogenesis, and neurocognitive and neurodegenerative disorders and most recently in studies of human and experimental placental malaria demonstrating a causal role for C5a-C5aR in altering placental angiogenesis and mediating adverse birth outcomes associated with malaria infection (19,22,60).…”
Section: In Contrast To C5arsupporting
confidence: 88%
See 1 more Smart Citation
“…This hypothesis is supported by our data from the present and previous in vitro and in vivo studies (17,25) and by observations in human CM (5, 8-10, 17, 34, 43, 45, 46, 52). Furthermore, our observations are consistent with a growing body of compelling evidence implicating a causal role for C5a-C5aR in the induction of proinflammatory mediators and antiangiogenic factors in multiple disease conditions that share features with cerebral malaria, including sepsis, ischemia-reperfusion injuries, pathological angiogenesis, and neurocognitive and neurodegenerative disorders and most recently in studies of human and experimental placental malaria demonstrating a causal role for C5a-C5aR in altering placental angiogenesis and mediating adverse birth outcomes associated with malaria infection (19,22,60).…”
Section: In Contrast To C5arsupporting
confidence: 88%
“…Instead, both the median survival and the changes in the inflammatory mediators (including HMGB-1) were similar in WT and C5L2 Ϫ/Ϫ mice. Lack of a functional role for C5L2 in ECM is consistent with observations in models of experimental placental malaria in which C5aR deficiency and antibody-mediated blockade of C5aR but not C5L2 significantly reduce fetal growth restriction and improve fetal viability (60). Collectively, these data support the view that, in the context of malaria pathogenesis, C5a appears to function predominantly through C5aR rather than C5L2.…”
Section: In Contrast To C5arsupporting
confidence: 86%
“…PM is associated with increased risk of adverse outcomes for both mother and fetus, including an increased risk of anemia, preterm birth, stillbirth, and delivery of low birth weight infants. During pregnancy, malaria-infected red blood cells accumulate in the placental intervillous blood spaces, resulting in altered placental angiogenesis and vascular flow, reduced nutrient and waste transfer, placental insufficiency, and a chronic localized proinflammatory environment (Fried and Duffy, 1996;Matteelli et al, 1997;Miller et al, 2002;Conroy et al, 2013). As such, optimization of pharmacological treatment of malaria in pregnancy is a global health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover in pre-clinical and clinical studies increased levels of C5a were associated with dysregulation of angiogenic factors (e.g. VEGF, endoglin, angiopoietin-1 and angiopoietin-2), placental vascular insufficiency, and an increased risk of adverse birth outcomes including LBW and stillbirth [14,15].…”
Section: Adverse Birth Outcomes In Placental Malariamentioning
confidence: 99%
“…However, dysregulated activation or control of the complement system is associated with several adverse pregnancy outcomes, such as preeclampsia and spontaneous abortion [12,13]. Human, pre-clinical models, and in vitro studies have shown that PM is associated with increased activation of the complement system, in particular enhanced generation of the pro-inflammatory component C5a [14,15]. In vitro, C5a can induce the synergistic release of both inflammatory mediators (e.g.…”
Section: Adverse Birth Outcomes In Placental Malariamentioning
confidence: 99%